Agreement of Potassium, Sodium, Glucose, and Hemoglobin Measured by Blood Gas Analyzer With Dry Chemistry Analyzer and Complete Blood Count Analyzer: A Two-Center Retrospective Analysis - Xie, Hongxiang; Lv, Shiyu; Chen, Sufeng; Pang, Zhenzhen; Ye, Deli; Guo, Jianzhuang; Xu, Wanju; Jin, Weidong (Frontiers in Medicine, 2022)
BACKGROUND: Here, we compared the consistency of sodium, potassium, glucose, and hemoglobin levels measured by blood gas analyzers (BGAs) and dry chemistry and complete blood count analyzers. METHODS: Data from two teaching hospitals, the Zhejiang Provincial People's Hospital (ZRY) and the Qianfoshan Hospital (QY), were retrospectively analyzed based on dry biochemistry and complete blood count analyzer results as the reference system (X) and BGA as the experimental system (Y). Plasma was used for biochemical analysis at the ZRY Hospital, and serum at the QY Hospital. Paired data from the respective hospitals were evaluated for consistency, and biases between methods were assessed by simple correlation, Passing–Bablok regression, and Bland–Altman analyses. RESULTS: The correlations of potassium, sodium, glucose, and hemoglobin measured by BGA and dry biochemistry and complete blood count analyzers were high, at 0.9573, 0.8898, 0.9849, and 0.9883 for the ZRY Hospital and 0.9198, 0.8591, 0.9764, and 0.8666, respectively, for the QY Hospital. The results of Passing–Bablok regression analysis showed that the predicted biases at each medical decision level were within clinically acceptable levels for potassium, sodium, glucose, and hemoglobin at the ZRY Hospital. Only the predicted bias of glucose was below the clinically acceptable medical decision levels at the QY Hospital, while potassium, sodium, and hemoglobin were not. Compared with the reference system, the mean bias for BGA measurements at the ZRY Hospital was -0.08 mmol/L (95%CI] -0.091– -0.069) for potassium, 1.2 mmol/L (95%CI 1.06–1.42) for sodium, 0.20 mmol/L (95%CI 0.167–0.228) for glucose, and -2.8 g/L for hemoglobin (95%CI -3.14–-2.49).The mean bias for potassium, sodium, glucose, and hemoglobin at the QY Hospital were -0.46 mmol/L (95% CI -0.475– -0.452), 3.7 mmol/L (95%CI 3.57– 3.85), -0.36 mmol/L (95%CI -0.433– - 0.291), and -8.7 g/L (95% CI -9.40– -8.05), respectively. CONCLUSION: BGA can be used interchangeably with plasma electrolyte results from dry biochemistry analyzers but does not show sufficient consistency with serum electrolyte results from dry biochemistry analyzers to allow data interchangeability. Good consistency was observed between BGA and plasma or serum glucose results from dry biochemistry analyzers. However, BGA-measured hemoglobin and hematocrit assay results should be treated with caution.